A clinical decision support system promotes the appropriate use of drugs in hospitalized patients with kidney impairment - Akihiro Sonoda (Journal of Pharmaceutical Health Care and Sciences)
Abstract The number of individuals with chronic kidney disease (CKD) is increasing worldwide, including in Japan. Patients with advanced CKD are at an increased risk of serious adverse drug events associated with hospitalization, life-threatening complications, and death. It is necessary to adjust the dosage of renally excreted drugs according to kidney function in patients with CKD. In addition, elderly patients and those with impaired kidney function are also at high risk of drug-induced nephrotoxicity due to nephrotoxic drugs, and special attention should be paid to changes in kidney function before and after administration. Hospitalized patients are more susceptible to acute kidney injury than outpatients, and care must be taken when administering renally excreted or nephrotoxic drugs. Clinical decision support systems (CDSSs) play an important role in preventing overdosage of renally excreted drugs and avoiding the inappropriate use of nephrotoxic drugs. This review discussed the effectiveness, issues, and potential of CDSSs for physicians’ prescriptions and pharmacists’ prescription audits before hospitalized patients with kidney impairment are administered renally excreted drugs or nephrotoxic drugs, and the follow-up of patients receiving them. Although inappropriate prescriptions of renally excreted drugs due to alerts to prescribers were reduced, prescribers may have ignored interruption alerts. Therefore, the acceptance rate of alerts by prescribers can be improved by minimizing interruptions to the prescriber workflow, specifying only high-severity alerts, and automatically inputting the dosage, administration frequency, and administration duration according to kidney function when the prescriber selects a drug when entering a prescription. Prescription audits by pharmacists using electronic alerts from the CDSS and dosage confirmation sheets were effective in preventing overdosing of renally excreted drugs. In addition, pharmacist interventions for patients at risk of acute kidney injury (AKI) using CDSS alerts may be useful in preventing a decrease in kidney function and the onset of AKI due to nephrotoxic drugs. Although the usefulness of CDSSs may be further improved in the future, further evaluation and improvement of CDSSs are required.